2023
DOI: 10.1039/d3cp02702c
|View full text |Cite
|
Sign up to set email alerts
|

Increase in anionic Fe3O4 nanoparticle-induced membrane poration and vesicle deformation due to membrane potential – an experimental study

Abstract: Membrane potential plays a significant role in various cellular processes while interacting with membrane active agents. So far, all the investigations of the interaction of nanoparticles (NPs) with lipid vesicles...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Furthermore, reports suggest that sugar concentration can also influence bending rigidity. Considering the significance of membrane potential 176 and protein channels in cell physiology, alterations in these factors can disrupt normal cellular functioning and lead to various diseases. Therefore, future research opportunities are identified to investigate the impact of membrane potential and channel-forming proteins on bending rigidity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reports suggest that sugar concentration can also influence bending rigidity. Considering the significance of membrane potential 176 and protein channels in cell physiology, alterations in these factors can disrupt normal cellular functioning and lead to various diseases. Therefore, future research opportunities are identified to investigate the impact of membrane potential and channel-forming proteins on bending rigidity.…”
Section: Discussionmentioning
confidence: 99%
“…If the pore fails to close, rupturing of cells or vesicles occurs. 4,5 It has been investigated that a pore can be induced in the membrane due to various reasons, such as applying external force using micropipettes, 6 electric field, 7–10 optical illumination, 11 binding of antimicrobial peptides, 12,13 pore-forming toxins, 14 nanoparticles, 15,16 etc. Among the known factors influencing pore formation and growth, pore edge tension, Γ (sometimes referred to as line tension), plays an important role in pore dynamics of the lipid bilayers.…”
Section: Introductionmentioning
confidence: 99%